2008
DOI: 10.1007/s10811-007-9297-x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for the development of an integrated seaweed-based aquaculture activity in Chile: determining the physiological capabilities of Macrocystis and Gracilaria as biofilters

Abstract: Seaweed production is a reality in Chile. More than ten species are commercially used to produce phycocolloids, fertilizers, plant growth control products, human food or animal fodder and feed additives. These multiple uses of algae offer a number of possibilities for coupling this activity to salmon, abalone and filter-feeder farming. In this context, different experiments carried out in Chile have demonstrated that Gracilaria chilensis and Macrocystis pyrifera have great potential in the development of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 33 publications
1
48
0
2
Order By: Relevance
“…Due to increasing concerns about the environmental impacts of aquaculture, a new method of aquaculture with a smaller ecological footprint has been developed. Integrated multi-trophic aquaculture (IMTA) has the potential to mitigate the environmental impacts of aquaculture (Buschmann et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to increasing concerns about the environmental impacts of aquaculture, a new method of aquaculture with a smaller ecological footprint has been developed. Integrated multi-trophic aquaculture (IMTA) has the potential to mitigate the environmental impacts of aquaculture (Buschmann et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds are used in IMTA systems for their nutrient-absorbing and sequestering properties. Nutrients excreted and egested by bivalves can be absorbed by macroalgae and recycled into valuable biomass (Newell 2004, Buschmann et al 2008, and this amount of nutrient waste can be effectively removed from the ecosystem. In addition, a number of studies have confirmed that suspension-feeding bivalves can exert top-down control on phytoplankton (Newell & Koch 2004, Wall et al 2008; larger nanoplankton will be removed in comparison with smaller (< 3 µm diameter) picoplankton species, thereby reducing turbidity (Newell 2004).…”
Section: Introductionmentioning
confidence: 99%
“…USA, Canada, Norway, Scotland, Ireland, Sweden and Germany; Buchholz 2004a, 2005;Chopin et al 2004;Barrington et al 2009;Broch et al 2013;Marinho et al 2015;Kraemer et al 2014;Kim et al 2015a) and Macrocystis in the eastern Pacific Ocean (e.g. Chile; Buschmann et al 2008). The kelp aquaculture industry in western countries has become one of the fastest growing industries.…”
Section: Saccharina and Undariamentioning
confidence: 99%
“…Considering a 10:1 DW:FW ratio and average values of nitrogen (Pyropia/Porphyra: 5.5%, Gracilaria: 3.0%, Kappaphycus/Eucheuma: 1.7%, kelp: 2.0% and Sargassum: 4.1%) and carbon (Pyropia/Porphyra: 38%, Gracilaria: 28%, Kappaphycus/Eucheuma: 29%, kelp: 30% and Sargassum: 34%), the total nitrogen and carbon removal by these five major aquaculture groups is approximately 54 million t of nitrogen per year and 700 million t of carbon per year (equivalent to 2600 million t of CO 2 ), respectively (Asare and Harlin 1983;Gerard 1997;Schaffelke and Klumpp 1998;Gevaert et al 2001;Schaffelke 2001;Chung et al 2002;Rawson et al 2002;Sahoo and Ohno 2003;Dean and Hurd 2007;Kim et al 2007Kim et al , 2014aKim et al , 2015aBuschmann et al 2008;Abreu et al 2009;Robertson-Andersson et al 2009;Levine and Sahoo 2010;Broch et al 2013). This is, in fact, a significant amount of carbon and nitrogen removal.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…However, the annual range is higher for G. chilensis at 1.2-35.6·µM·g(DW) −1 ·h −1 in comparison to 3.7-16.9 µM·g(DW) −1 ·h −1 for M. pyrifera. The incorporation of seaweed species with different light requirements to an IMTA system allows for the utilization of different water column depths and subsequently increases their efficiency and effectiveness as biofilters [138].…”
Section: Integrated Multi-trophic Aquaculture (Offshore and On-land)mentioning
confidence: 99%